The management model of Ceking Terrace Tegallalang based on sustainable tourism development - Pande Putu Tobi Sukmadiarta; Ni Nyoman Sunariani (Review of Management, Accounting, and Business Studies, 2023)
Indonesia's rich natural beauty and biodiversity made it a prime destination for both domestic and international tourists, significantly contributing to the nation's economic growth. The tourism sector, closely linked to sustainable development, required careful management to ensure the continuity of natural and socio-cultural resources. This study examined the management model of the Ceking Terrace tourist attraction in Tegallalang Village, Bali, a region renowned for its terraced rice fields and cultural richness. Employing a qualitative descriptive approach, data were collected through observation, documentation, and in-depth interviews with various stakeholders, including management officials, local community leaders, and tourists. The study revealed that the Ceking Terrace was managed using the Planning, Organizing, Actuating, and Controlling (POAC) model, which effectively enhanced local revenue and community welfare. The management focused on maintaining environmental sustainability, socio-cultural values, and economic benefits, aligning with the Tri Hita Karana principle that emphasized harmony between humans, nature, and spirituality. Despite its popularity, the site faced challenges such as inadequate public facilities, which hindered optimal tourist satisfaction and accessibility. Recommendations for improving the management of Ceking Terrace included better recruitment and salary distribution for employees, enhancing public facilities, and fostering partnerships with travel agents to boost tourist visits. The study underscored the importance of sustainable tourism development practices to ensure long-term benefits for both the local community and the environment.